2012
DOI: 10.4103/0019-5049.98774
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-operative rectal diclofenac suppository on post-operative analgesic requirement in cleft palate repair: A randomised clinical trial

Abstract: Background:Opioid analgesics used for analgesia are associated with sedation, respiratory depression and post-operative nausea and vomiting. Non-steroidal anti-inflammatory drugs such as diclofenac are a safe and effective alternative with opioid-sparing effect.Objective:To evaluate the effectiveness of pre-operative rectal diclofenac suppository (1 mg/kg) in cleft palate repair for post-operative analgesia and reduction in post-operative opioid requirements.Study Design:A randomized clinical trial.Methods:Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
(15 reference statements)
2
14
0
Order By: Relevance
“…[20][21][22][23][24]33,34 The utility of acetaminophen, nonsteroidal anti-inflammatory drugs, and opioids for postoperative pain management were also studied. [25][26][27][28]32 Opioid-sparing effects were observed in multiple studies. 22,[24][25][26]28,33 The use of adjuvants (i.e., dexmedetomidine) in anesthetics for nerve blocks resulted in prolonged effective analgesia compared to controls.…”
Section: Cleft Palatoplastymentioning
confidence: 99%
“…[20][21][22][23][24]33,34 The utility of acetaminophen, nonsteroidal anti-inflammatory drugs, and opioids for postoperative pain management were also studied. [25][26][27][28]32 Opioid-sparing effects were observed in multiple studies. 22,[24][25][26]28,33 The use of adjuvants (i.e., dexmedetomidine) in anesthetics for nerve blocks resulted in prolonged effective analgesia compared to controls.…”
Section: Cleft Palatoplastymentioning
confidence: 99%
“…Reference [ 15 ] divided the instructional content into a 5-stage intervention process and taught imitative behavior to young children with autism. The SCERTS model developed by [ 16 ] refers to seven intervention principles, including an emphasis on the functional use of language and communication in all natural contexts; consideration of the child's emotional regulation and its impact on communication, social interaction, and learning; and the integration of behavioral problems into social communication training programmes and the analysis of behavioral functioning and positive behavioral treatment. Reference [ 17 ] combined DTT orientation and PRT teaching interventions to improve joint attention in children with autism and found that both children showed progress in joint attention after the intervention; [ 18 ] mainly referred to an intervention programme that divided the training process into tabletop and floor time, with the therapist and parents as the intervenor, and analysed behavioral records from the intervention process; [ 19 ] conducted a joint attention intervention with a child with autism.…”
Section: Related Workmentioning
confidence: 99%
“…There is abundant evidence in the literature proving the effectiveness of diclofenac in postoperative pain management. [ 7 8 9 ] When two different agents targeted at a single pharmacological effect are used in synergism, the said combination allows the reduction in the dose of individual drugs without compromising on the quality of the effect, rendering a wider margin of safety. Thus in our study, we sought to compare the effectiveness of the combination of paracetamol and diclofenac with that of paracetamol alone in combating postoperative pain.…”
Section: Discussionmentioning
confidence: 99%